A self-contained GIM-aided Abel retrieval method to improve GNSS-Radio Occultation retrieved electron density profiles - Tulasiram, S.; Su, Shin-Y; Tsai, Lung-Chi; Liu, Chao Han (My University, 2015)
A self-contained global ionospheric maps (GIM)-aided Abel retrieval method is adopted that can account for spherical non-uniformity along the radio wave path in the vicinity of the radio occultation (RO) region using the asymmetry factors derived from global background NmF2 maps. This procedure does not require any supplementary data sources to augment the Abel retrieval in order to represent the horizontal gradients in the ionosphere. This simulation study demonstrates that when sufficiently dense RO observations are available, the NmF2 values initially derived from classical Abel retrieval (with the assumption of spherical symmetry) are sufficiently good and useful to represent the spherical non-uniformities in electron density distribution. The Ne(h) profiles retrieved from this Abel retrieval procedure aided with asymmetry factors provide significant improvement compared to classical Abel retrieval at both F- and E-regions. The artificial large-scale structures, such as wave number-3 latitudinal structure and plasma caves underneath the equatorial ionization anomaly crests, were largely eliminated. This improved retrieval procedure also reduces the computational complexity and is suitable when the number of occultations increased by many times in the future when FORMOSAT-7/COSMIC-2 (F7/C2) and other RO missions become operational. The computation simplicity in this self-contained GIM-aided Abel retrieval procedure enables more accurate retrieval of Ne(h) profiles in near real time.
Keywords: GNSS-Radio Occultation; Ionosphere; Electron density profiles; Abel retrieval